Архітектурно-планувальні рішення медіатек - світовий досвід - Пилипишин, Б. В.; Кравченко, Ірина Леонідівна; Kravchenko, I. L.; Pylypyshyn, B. V. (КНУБА, 2019)
The article is reviewing the practice of designing and functional organization of the space in libraries and media libraries based on the world experience. The article is researching questions of architectural and planning principles and techniques used in modern media centers. After analyzing the foreign experience of forming architectural and planning decisions of public libraries, the basic principles and methods of solving the formation are identified, namely: the combination of various functions in a continuous space, the connection with the environment, the use of sunny lighting, the transformation and zoning of space, rethinking of traditional library planning. У статті розглянуто практику проектування та функціональну організацію простору в бібліотеках та медіатеках на базі світового досвіду, формування архітектурно-планувального рішення публічних бібліотек, виявлено основні принципи та прийоми вирішення об’ємно-просторової структури і формоутворення.
Keywords: медіатека; медіацентр; медійний простір; сучасна бібліотека; інформаційний центр; media library; media space; media center; modern library; information center